Vertical mergers, foreclosure and raising rivals' costs: Experimental evidence - Hans-Theo Normann (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2010)
The hypothesis that vertically integrated firms have an incentive to foreclose the input market because foreclosure raises its downstream rivals' costs is the subject of much controversy in the theoretical industrial organization literature. A powerful argument against this hypothesis is that, absent commitment, such foreclosure cannot occur in Nash equilibrium. The laboratory data reported in this paper provide experimental evidence in favor of the hypothesis. Markets with a vertically integrated firm are signifiantly less competitive than those where firms are separate. While the experimental results violate the standard equilibrium notion, they are consistent with the quantalresponse generalization of Nash equilibrium.
Keywords: C72; C90; D43; 330; experimental economics; foreclosure; quantal response equilibrium; raising rival's costs; vertical integration; Kartell; Vertikale Konzentration; Theorie; Spieltheorie; Test